The Social Nature of Speech in the Film Anak Lanang: A Sociolinguistic Pragmatic Study - Nisa Nur Fitria; Izzuddin Mustafa (Penerbit Yayasan Daarul Huda Kruengmane, 2026)
This study aims to examine speech in the short film Anak Lanang (2017) by Wahyu Agung Prasetyo using a sociolinguistic pragmatic approach. The purposes of this study are to identify the types of speech acts based on Austin and Searle's theories, to analyze speech events using Dell Hymes' SPEAKING components, and to uncover the social functions reflected in dialogues in the Javanese Yogyakarta dialect. The research method employs qualitative data analysis with observation, note-taking, and dialogue transcript techniques. The findings reveal that the film dialogues contain five types of illocutionary speech acts, namely assertives, directives, expressives, commissives, and negative assertives, along with code-switching phenomena from Javanese to digital terminology. The informal setting on top of a becak creates egalitarian speech, while cross-generational interaction emerges through the dynamics of authority. Five social functions identified include social solidarity, family identity expression, behavioral regulation, cultural value transmission, and social reality reflection. These findings confirm that speech in the film constitutes a complex social action reflecting the dialectic between Javanese local traditions and digital modernity.